Composite current collector and preparation method and application thereof
By growing the rod-like structure in situ on the coating layer of the coating current collector, the problem of insufficient adhesion of the existing coating aluminum foil current collector is solved, and better combination of the positive electrode active material and the coating layer is achieved, and the electrochemistry of lithium batteries is improved. performance.
Patent Information
- Application Number
- CN202411547429.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The current coated aluminum foil current collector has low adhesion, which affects the connection between the positive electrode active material and the coated layer, resulting in poor performance of lithium batteries.
A specific rod-like structure with a specific composition is grown in situ on the coating layer of the coated current collector, including the rod-like body and carbon particles embedded in the body, increasing the complexity and roughness of the surface, thereby enhancing the bonding force.
By increasing the contact area and degree of embedding with the positive electrode active material during rolling, the adhesive force and peel strength of the current collector and the positive electrode active material are effectively improved, and the conductivity and electrochemical properties of the electrode are improved.
Smart Images

Figure CN119419281A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries and relates to a composite current collector and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have been widely accepted in many fields such as consumer electronics, transportation, power tools and energy storage. As one of the key components, the current collector in lithium-ion batteries plays a relatively important role. Its main functions are: carrying electrode active materials, collecting and outputting the current generated by the active materials, and inputting the electrode current to the active materials.
[0003] Aluminum foil current collector refers to a composite material formed by combining aluminum foil with other materials (such as paper, plastic film, coating, etc.). This composite material can give aluminum foil new properties and functions to meet the needs of different industries. In the lithium battery industry, in order to improve the performance of lithium batteries, the strategy of using carbon-coated current collectors can increase the rate of lithium batteries and improve the performance of lithium batteries. However, the low adhesion of the carbon-coated aluminum foil current collector affects the subsequent coating of the positive electrode active material. Therefore, it is necessary to develop and manufacture a carbon-coated current collector with higher adhesion to ensure the connection between the positive electrode active material and the carbon coating layer. Summary of the invention
[0004] In view of the above problems existing in the prior art, the purpose of the present invention is to provide a composite current collector and a preparation method and application thereof.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] In the first aspect, the present invention provides a composite current collector, comprising a carbon-coated current collector, the carbon-coated current collector comprising a current collector substrate and a carbon-coated layer located on the surface of the current collector substrate, a rod-like structure in situ grown on the carbon-coated layer, the rod-like structure comprising a rod-like body and carbon particles embedded in the rod-like body, the material of the rod-like body comprising Ni and Mo.
[0007] The present invention does not specifically limit the type of the current collector substrate, and it may be, for example, aluminum foil.
[0008] The present invention increases the complexity and roughness of the surface by in-situ growing a rod-like structure of a specific composition on the carbon-coated layer of the carbon-coated current collector, wherein the roughness refers to the unevenness and roughness of the surface of the carbon-coated layer, which has an important influence on the adhesion and performance of the carbon-coated current collector. The higher the roughness of the surface of the carbon-coated layer, the more mechanical locking points it provides, thereby making the adhesion stronger. Therefore, the composite current collector of the present invention increases the contact area and embedding degree with the positive electrode active material during rolling, and the positive electrode active material and the carbon-coated layer can be better combined, effectively improving the adhesion and peeling strength of the current collector and the positive electrode active material. At the same time, since carbon particles are embedded in the rod-like body, the composite current collector is guaranteed to have good conductivity, which is conducive to improving the electrochemical performance of the electrode prepared using it.
[0009] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0010] Preferably, the material of the rod-shaped body is doped or undoped NiMoO4, wherein the doping element is at least one of P, S, C or Se.
[0011] Preferably, the rod-like structure appears as a straw on the carbon-coated layer, wherein the straw-like shape is: a plurality of the rod-like structures are clustered and divergent, and the angle θ between the rod-like structure and the plane of the carbon-coated layer is mainly in the range of 30°-90°. Exemplarily, θ may be 30°, 35°, 40°, 45°, 50°, 55°, 60°, 65°, 70°, 75°, 80°, 85° or 90°, etc.
[0012] Preferably, the rod-like structure is a prismatic microrod with a rectangular cross section, the length of the rectangle is in the range of 0.03 μm-0.07 μm, for example, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm or 0.07 μm, etc.; the width of the rectangle is in the range of 0.02 μm-0.06 μm, for example, 0.02 μm, 0.03 μm, 0.04 μm , 0.05μm or 0.06μm, etc.; the rod length of the rod-like structure is in the range of 0.5μm-1.2μm, for example, it can be 0.5μm, 0.55μm, 0.6μm, 0.65μm, 0.7μm, 0.75μm, 0.8μm, 0.85μm, 0.9μm, 0.95μm, 1μm, 1.05μm, 1.1μm, 1.15μm or 1.2μm, etc.
[0013] Preferably, the angle θ is in the range of 45°-90°, more preferably in the range of 60°-90°.
[0014] In a second aspect, the present invention provides a method for preparing the composite current collector as described in the first aspect, the preparation method comprising the following steps:
[0015] (1) preparing a mixed salt solution using nickel salt, molybdenum salt and solvent;
[0016] (2) placing the mixed salt solution and the carbon-coated current collector in a reaction container, sealing the reaction container and heating it, and reacting them at a certain temperature and pressure to obtain the composite current collector.
[0017] The method of the present invention can utilize the carbon-coated current collector to in-situ grow a rod-like structure, wherein the rod-like body of the rod-like structure includes Ni and Mo. At the same time, since the carbon-coated current collector contains carbon elements, carbon particles can be introduced onto the rod-like body after the reaction in a sealed reaction container.
[0018] The composite current collector prepared by the method of the present invention effectively improves the adhesion and peeling strength between the current collector and the positive electrode active material, has good conductivity, and can improve the electrochemical performance of the electrode of the battery prepared by using the composite current collector.
[0019] The method of the present invention is simple, the experimental operation and experimental steps are greatly reduced, the usage of machinery and equipment and the difficulty of operation are reduced, thereby reducing the production cost and the maintenance cost of the equipment, and is conducive to popularization and use.
[0020] In the method of the present invention, since the carbon-coated current collector is light in weight and thin in thickness, placing it together with the mixed salt solution in a reaction container can easily cause the carbon-coated current collector to be sucked to the bottom of the reaction container under the action of water pressure. In this case, it is necessary to uncover the carbon-coated current collector from the bottom of the reaction container so that the pressure on both sides of the carbon-coated current collector is equal, so that the carbon-coated current collector is suspended in the solution, thereby growing microstructures on both sides.
[0021] In one embodiment, the reaction vessel is a reactor.
[0022] Preferably, the nickel salt in step (1) includes NiSO4·6H2O.
[0023] Preferably, the molybdenum salt in step (1) includes Na2MoO4·2H2O and / or ammonium molybdate.
[0024] Preferably, in step (1), the molar ratio of the nickel element in the nickel salt to the molybdenum element in the molybdenum salt is greater than or equal to 1.5:1, for example, it can be 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 3.8:1, 4:1, 4.3:1, 4.5:1, 4.7:1, 4.8:1, 5:1, 5.3:1, 5.5:1, 5.7:1 or 6:1, etc. In this preferred range, the optimal interface microenvironment can be obtained, thereby improving the coating stripping force. The technical principle is as follows: the nickel element can promote the number and density of the rod-like structure. If it is to grow into abundant straw-like microrods, sufficient Ni2+ and an appropriate amount of molybdenum ions are required. However, the number of microrod structures is not the more the better. Exceeding a certain number will reduce the toughness of the composite current collector. Therefore, it is more preferred that the molar ratio of the nickel element to the molybdenum element is in the range of (1.5-6):1.
[0025] In one embodiment, a mixed salt solution is prepared in the following manner: a nickel salt (e.g., NiSO4·6H2O) and a solvent are mixed and stirred until the solution is clear and transparent to obtain a first solution; a molybdenum salt (Na2MoO4·2H2O) and a solvent are mixed and stirred until the solution is clear and transparent to obtain a second solution; the first solution and the second solution are mixed and stirred evenly to obtain a mixed salt solution.
[0026] Preferably, the pH of the mixed salt solution in step (1) is 6.5-7.5, for example, it can be 6.5, 6.6, 6.8, 7, 7.1, 7.2, 7.3, 7.4 or 7.5, etc.
[0027] For some salts (such as NiSO4·6H2O and Na2MoO4·2H2O), the solution obtained after adding the solvent is neutral, so a mixed salt solution that meets the pH requirements can be directly obtained without adjusting the pH of the solution; while for some salts (such as ammonium molybdate), the pH of the solution obtained after adding the solvent is less than 6.5, so a pH adjuster needs to be added to adjust the pH to the required pH.
[0028] Preferably, when the solvent used in the preparation process of the carbon-coated current collector is water, the solvent in step (1) includes at least one of dimethylformamide, N-methylpyrrolidone (NMP) and methyl ethyl ketone (MEK). Under this condition, the reaction in step (2) is a solvent thermal reaction. Since the solvent used in the preparation process of the carbon-coated current collector is water, the problem of damaging the integrity of the coating of the carbon-coated current collector will not occur during the reaction in step (2).
[0029] Preferably, when the solvent used in the preparation process of the carbon-coated current collector is an oil-based solvent, the solvent in step (1) is water. In one embodiment, the oil-based solvent is N-methylpyrrolidone. Under this condition, the reaction in step (2) is a hydrothermal reaction. Since the solvent used in the preparation process of the carbon-coated current collector is an oil-based solvent, the problem of damaging the integrity of the coating of the carbon-coated current collector will not occur during the reaction in step (2).
[0030] Preferably, the oil-based solvent includes N-methylpyrrolidone.
[0031] Preferably, when the carbon-coated current collector is a sodium electro-coating current collector, and the carbon-coating slurry used in the preparation process of the sodium electro-coating current collector contains a cross-linking agent, the solvent in step (1) is water. Under this condition, the reaction in step (2) is a hydrothermal reaction. Since the carbon-coating slurry used in the preparation process of the sodium electro-coating current collector contains a cross-linking agent, it has good water resistance, and the problem of damaging the coating integrity of the carbon-coated current collector will not occur during the reaction in step (2).
[0032] Preferably, the cross-linking agent includes at least one of methacrylic acid, methvinyl acid and isopropyl acrylic acid.
[0033] Preferably, in step (2), the temperature is heated to 120°C-240°C, for example, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C, etc.
[0034] Preferably, during the reaction in step (2), the pressure in the reaction container is 2-3 atmospheres, for example, 2 atmospheres, 2.2 atmospheres, 2.5 atmospheres, 2.7 atmospheres or 3 atmospheres.
[0035] Preferably, the reaction time of step (2) is 8 h to 18 h, for example, it can be 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h or 18 h.
[0036] Optionally, the drying method is oven drying, and the drying temperature is 50°C-60°C, for example, 50°C, 52°C, 53°C, 55°C, 58°C or 60°C.
[0037] The present invention does not limit the drying time, and those skilled in the art can select the time according to actual needs.
[0038] As a preferred technical solution of the preparation method of the present invention, the preparation method of the carbon-coated current collector in step (2) comprises the following steps:
[0039] (A) dispersing the raw materials of the carbon coating layer in a solvent to obtain a carbon coating slurry;
[0040] (B) coating the carbon-coated slurry on the surface of a current collector substrate, and forming a carbon-coated layer on the surface of the current collector substrate after drying to obtain the carbon-coated current collector.
[0041] Preferably, the raw materials of the carbon coating layer in step (A) include a conductive agent and a binder.
[0042] Preferably, the conductive agent includes carbon powder, and preferably also includes graphite powder.
[0043] Preferably, the mass proportions of the carbon powder and the graphite powder in the conductive agent are 70%-100% and 0%-30% respectively, wherein the mass proportion of the carbon powder in the conductive agent is "70%-100%, for example, it can be 70%, 72%, 75%, 78%, 80%, 85%, 90%, 95% or 100%, etc.; the mass proportion of the graphite powder in the conductive agent is "0%-30%, for example, it can be 0%, 1%, 2%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 28% or 30%, etc. Among them, when the mass proportion of the carbon powder is 100%, it means that the conductive agent is composed of carbon powder; when the mass proportion of the graphite powder is 0%, it means that the conductive agent does not contain graphite powder.
[0044] Preferably, the binder comprises at least one of acrylate, polyacrylic acid, modified polyacrylic acid or waterborne polyurethane, preferably modified polyacrylic acid.
[0045] Preferably, the binder is a modified polyacrylic acid glue having a solid content of 15%-30%, for example, 15%, 16%, 17%, 18%, 20%, 22%, 24%, 25%, 26%, 28% or 30%, etc.; the viscosity of the modified polyacrylic acid glue is 200mPa.s-1500mPa.s, for example, 200mPa·s, 300mPa·s, 400mPa·s, 500mPa·s. s, 550mPa·s, 600mPa·s, 650mPa·s, 700mPa·s, 750mPa·s, 800mPa·s, 850mPa·s, 900mPa·s, 950 mPa·s, 1000mPa·s, 1050mPa·s, 1100mPa·s, 1200mPa·s, 1300mPa·s, 1400mPa·s or 1500mPa·s, etc.
[0046] Preferably, the raw materials for the carbon coating layer in step (A) also include a wetting agent.
[0047] Preferably, the wetting agent comprises at least one of polyether siloxane, modified polyether siloxane and alcohols, preferably modified polyether siloxane.
[0048] Modified polyether siloxane is a special type of siloxane material. It modifies the properties of siloxane by introducing polyether segments to improve its flexibility, chemical resistance and low temperature performance.
[0049] The structure of modified polyether siloxane is composed of a siloxane skeleton and a polyether segment, which are connected by copolymerization or grafting reaction. This structure makes the modified polyether siloxane have good mechanical properties, thermal stability and chemical stability.
[0050] The present invention does not specifically limit the source of the modified polyether siloxane, for example, it can be a commercially available product, an exemplary source is: purchased from Dow Corning Company, USA, model: DC-595.
[0051] Preferably, the amount of the wetting agent is 3%-20% of the total mass of the reaction system, for example, 3%, 4%, 5%, 6%, 7%, 8%, 10%, 12%, 13%, 14%, 15%, 17%, 18% or 20%, etc. Here, the total mass of the reaction system refers to the mass of all liquids after the wetting agent is added.
[0052] As a preferred technical solution of the preparation method of the present invention, step (A) comprises:
[0053] S1 adds a conductive agent to the adhesive solution and disperses the conductive agent to obtain a first material;
[0054] S2: adding a wetting agent to the first material, stirring and then homogenizing to obtain a carbon-coated slurry.
[0055] In the present invention, the adhesive glue liquid is the abbreviation of the adhesive in the form of glue liquid.
[0056] Preferably, step S1 comprises: firstly adding a part of the conductive agent to the adhesive glue, performing a first high-speed stirring, and then adding the remaining conductive agent to the obtained material, and performing a second high-speed stirring.
[0057] Preferably, the portion of the conductive agent accounts for 40%-60% of the total amount of the conductive agent, for example, it may be 40%, 42%, 44%, 45%, 48%, 50%, 53%, 55%, 57% or 60%, etc.
[0058] Preferably, the rotation speed of the first high-speed stirring is 2000rpm-2600rpm, for example, it can be 2000rpm, 2100rpm, 2150rpm, 2200rpm, 2250rpm, 2300rpm, 2350rpm, 2400rpm, 2500rpm, 2550rpm or 2600rpm.
[0059] Preferably, the first high-speed stirring time is 30 min-60 min, for example, it can be 30 min, 35 min, 38 min, 40 min, 43 min, 46 min, 48 min, 50 min, 53 min, 56 min or 60 min.
[0060] Preferably, the rotation speed of the second high-speed stirring is 2000rpm-2600rpm, for example, it can be 2000rpm, 2100rpm, 2150rpm, 2200rpm, 2250rpm, 2300rpm, 2350rpm, 2400rpm, 2500rpm, 2550rpm or 2600rpm.
[0061] Preferably, the second high-speed stirring time is 60 min-90 min, for example, it can be 60 min, 65 min, 70 min, 75 min, 80 min, 85 min or 90 min.
[0062] Preferably, the stirring speed in step S2 is 10 rpm-15 rpm, for example, it can be 10 rpm, 11 rpm, 12 rpm, 13 rpm or 15 rpm.
[0063] Preferably, the stirring time in step S2 is 30 min-45 min, for example, it can be 30 min, 35 min, 38 min, 40 min, 43 min or 45 min.
[0064] The present invention does not specifically limit the number of homogenization treatments, which generally suffices to be greater than 2 times, such as 2 times, 3 times or 4 times. The number of homogenization treatments can be determined according to actual needs in the art.
[0065] Preferably, the pressure of the homogenization treatment in step S2 is 300 bar-600 bar, for example, it can be 300 bar, 325 bar, 350 bar, 370 bar, 400 bar, 450 bar, 475 bar, 500 bar, 520 bar, 550 bar, 580 bar or 600 bar.
[0066] Preferably, the preparation method further comprises:
[0067] After step S1 and before step S2, perform the following steps:
[0068] (a) adding a solvent to the first material to reduce the concentration of the slurry, and dispersing at a high speed of 2000 rpm to 2600 rpm (for example, 2000 rpm, 2100 rpm, 2150 rpm, 2200 rpm, 2250 rpm, 2300 rpm, 2350 rpm, 2400 rpm, 2500 rpm, 2550 rpm or 2600 rpm, etc.) for 30 min to 45 min (for example, 30 min, 35 min, 38 min, 40 min, 43 min or 45 min, etc.).
[0069] (b) using a pH adjuster to adjust the pH of the slurry obtained in step (a) to 5-7 (for example, 5, 5.5, 5.8, 6, 6.5 or 7, etc.).
[0070] Preferably, the added amount of the pH regulator is 5wt%-10wt% of the binder glue, for example, it can be 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt% or 10wt% etc.
[0071] In a third aspect, the present invention provides a pole piece, comprising a current collector and an active layer arranged on the surface of the current collector, wherein the current collector is the composite current collector described in the first aspect or the composite current collector prepared by the method described in the second aspect.
[0072] The electrode sheet in the present invention can be a positive electrode sheet or a negative electrode sheet. For a positive electrode sheet, the current collector is a positive electrode current collector and the active layer is a positive electrode active layer; for a negative electrode sheet, the current collector is a negative electrode current collector and the active layer is a negative electrode active layer.
[0073] In one embodiment, the positive electrode current collector is the composite current collector described in the first aspect, wherein the current collector substrate is aluminum foil.
[0074] In one embodiment, the positive electrode material layer includes a positive electrode active material, a binder, and optionally a conductive agent.
[0075] In one embodiment, the negative electrode current collector is the composite current collector described in the first aspect, wherein the current collector substrate is copper foil.
[0076] In one embodiment, the negative electrode material layer includes a negative electrode active material, a binder, and optionally a conductive agent.
[0077] In a fourth aspect, the present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet and / or the negative electrode sheet is selected from the electrode sheet described in the third aspect.
[0078] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0079] Compared with the prior art, the present invention has the following beneficial effects:
[0080] (1) The present invention increases the complexity and roughness of the surface by in-situ growing a rod-like structure of a specific composition on the carbon-coated layer of the carbon-coated current collector, thereby increasing the contact area and embedding degree with the positive electrode active material during rolling, so that the positive electrode active material and the carbon-coated layer can be better combined, effectively improving the adhesion and peeling strength between the current collector and the positive electrode active material. At the same time, since carbon particles are embedded in the rod-like body, the composite current collector is guaranteed to have good conductivity, which is conducive to improving the electrochemical performance of the electrode prepared using the composite current collector.
[0081] (2) The method of the present invention is simple, the experimental operation and experimental steps are greatly reduced, the usage of machinery and equipment and the difficulty of operation are reduced, thereby reducing the production cost and the maintenance cost of the equipment, which is conducive to promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS
[0082] Figure 1 and Figure 2 These are scanned images of the carbon-coated layer in the composite current collector prepared in Example 1 at different magnifications. DETAILED DESCRIPTION
[0083] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0084] The embodiments of the present invention are described in detail below so that the advantages and features of the invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0085] In the embodiments of the present invention, the purchase sources of various raw materials are as follows:
[0086] The modified polyacrylic acid glue was purchased from Sinopharm Chemical Reagent Co., Ltd., with an average molecular weight of MW-5000, a solid content of 20%, and a viscosity of 1000 mPa·s.
[0087] Modified polyether siloxane can be purchased from Sinopharm Group with 99% purity and is produced by Beijing Wokai Biotechnology Co., Ltd.
[0088] Example 1
[0089] This embodiment provides a composite current collector, including a carbon-coated current collector, wherein the carbon-coated current collector includes a current collector substrate and a carbon-coated layer located on the surface of the current collector substrate, a rod-like structure is in-situ grown on the carbon-coated layer, and the rod-like structure includes a rod-like body and carbon particles embedded in the rod-like body.
[0090] The current collector substrate is aluminum foil, and the material of the rod-shaped body is NiMoO4.
[0091] The rod-like structures appear as straws on the carbon coating layer, wherein the straws are: a plurality of the rod-like structures are clustered and divergent, and an angle θ between the rod-like structures and the plane of the carbon coating layer is mainly in the range of 30°-90°.
[0092] Combination Figure 1 and Figure 2 It can be seen that the rod-like structure is a prismatic microrod with a rectangular cross section. The length of the rectangle is in the range of 0.03 μm-0.07 μm, the width of the rectangle is in the range of 0.02 μm-0.06 μm, and the rod length of the rod-like structure is in the range of 0.5 μm-1.2 μm.
[0093] This embodiment also provides a method for preparing the above-mentioned composite current collector, comprising the following steps:
[0094] (1) Preparation of carbon-coated current collector:
[0095] S1: Mix the modified polyacrylic acid glue with water, and slowly stir at a speed of 600 rpm for 30 minutes to obtain a diluted polyacrylic acid glue (viscosity of 800 mPa·s).
[0096] S2: First dispersion: Mix carbon powder and graphite powder in a mass ratio of 70:30 to obtain a conductive agent, add 50% of the conductive agent to the glue obtained in step S1, and disperse at a high speed of 2000 rpm for 30 minutes.
[0097] S3 Second dispersion: Continue to add 50% of the conductive agent and disperse at a high speed of 2600 rpm for 30 minutes.
[0098] S4 third dispersion: add water to reduce the viscosity of the slurry to prevent the slurry from being too viscous to be dispersed evenly, and disperse at a high speed of 2000rpm for 30min.
[0099] S5 tests the slurry pH and adjusts the slurry pH to 5 with water and sodium bicarbonate, because a slurry pH > 7 will cause a sharp increase in viscosity.
[0100] S6 was fully stirred and dispersed, and the slurry was dispersed at a high speed of 2250 rpm for 60 min.
[0101] S7: Add a wetting agent (modified polyether siloxane) in an amount of 10% of the total mass of the reaction system. After adding, slowly stir at 10 rpm for 45 minutes. Vacuum to remove bubbles, and homogenize at a pressure of 300 bar to obtain a carbon-coated slurry.
[0102] S8: coating the carbon-coated slurry obtained in step S7 on the surface of the aluminum foil, and forming a carbon-coated layer on the surface of the aluminum foil after drying to obtain a carbon-coated current collector.
[0103] (2) NiSO4·6H2O, Na2MoO4·2H2O and NMP are mixed to obtain a mixed salt solution, wherein the molar ratio of nickel element to molybdenum element is 4:1.
[0104] (3) The mixed salt solution obtained in step (2) and the carbon-coated current collector obtained in step (1) are placed in a Teflon high-pressure reactor, and the carbon-coated current collector is gently opened from the bottom of the reactor to suspend it in the solution. The reactor is sealed and reacted at 180°C for 12 hours. The pressure in the reactor is 2.2 atmospheres. After cooling to room temperature, the sample is taken out, placed in an oven, and dried at 60°C for 12 hours to obtain a composite current collector.
[0105] Example 2
[0106] This embodiment provides a composite current collector, including a carbon-coated current collector, wherein the carbon-coated current collector includes a current collector substrate and a carbon-coated layer located on the surface of the current collector substrate, a rod-like structure is in-situ grown on the carbon-coated layer, and the rod-like structure includes a rod-like body and carbon particles embedded in the rod-like body.
[0107] The current collector substrate is aluminum foil, and the material of the rod-shaped body is NiMoO4.
[0108] The rod-like structures appear as straws on the carbon coating layer, wherein the straws are: a plurality of the rod-like structures are clustered and divergent, and an angle θ between the rod-like structures and the plane of the carbon coating layer is mainly in the range of 30°-90°.
[0109] The rod-like structure is a prismatic microrod with a rectangular cross section. The length of the rectangle is in the range of 0.03 μm-0.07 μm, the width of the rectangle is in the range of 0.02 μm-0.06 μm, and the rod length of the rod-like structure is in the range of 0.5 μm-1.2 μm.
[0110] This embodiment also provides a method for preparing the above-mentioned composite current collector, comprising the following steps:
[0111] (1) Preparation of carbon-coated current collector:
[0112] S1: Mix the modified polyacrylic acid glue with water, and slowly stir at a speed of 600 rpm for 30 minutes to obtain a diluted polyacrylic acid glue (viscosity of 800 mPa·s).
[0113] S2: First dispersion: Mix carbon powder and graphite powder in a mass ratio of 80:20 to obtain a conductive agent, add 40% of the conductive agent to the glue obtained in step S1, and disperse at a high speed of 2600 rpm for 40 minutes.
[0114] S3 Second dispersion: Continue to add 60% of the conductive agent and disperse at a high speed of 2000 rpm for 90 minutes.
[0115] S4 third dispersion: add water to reduce the viscosity of the slurry to prevent the slurry from being too viscous to be dispersed evenly, and disperse at a high speed of 2400rpm for 30min.
[0116] S5 tests the slurry pH and adjusts the slurry pH to 6 with water and sodium bicarbonate, because a slurry pH > 7 will cause a sharp increase in viscosity.
[0117] S6 was fully stirred and dispersed, and the slurry was dispersed at a high speed of 2300 rpm for 55 min.
[0118] S7: Add a wetting agent (modified polyether siloxane) in an amount of 10% of the total mass of the reaction system. After adding, slowly stir at 15 rpm for 30 minutes. Vacuum to remove bubbles, and homogenize at a pressure of 600 bar to obtain a carbon-coated slurry.
[0119] S8: coating the carbon-coated slurry obtained in step S7 on the surface of the aluminum foil, and forming a carbon-coated layer on the surface of the aluminum foil after drying to obtain a carbon-coated current collector.
[0120] (2) NiSO4·6H2O, Na2MoO4·2H2O and NMP are mixed to obtain a mixed salt solution, wherein the molar ratio of nickel element to molybdenum element is 6:1.
[0121] (3) The mixed salt solution obtained in step (2) and the carbon-coated current collector obtained in step (1) are placed in a Teflon high-pressure reactor, and the carbon-coated current collector is gently opened from the bottom of the reactor to suspend it in the solution. The reactor is sealed and reacted at 220°C for 9 hours. The pressure in the reactor is 2.8 atmospheres. After cooling to room temperature, the sample is taken out, placed in an oven, and dried at 55°C for 11 hours to obtain a composite current collector.
[0122] Example 3
[0123] This embodiment provides a composite current collector, including a carbon-coated current collector, wherein the carbon-coated current collector includes a current collector substrate and a carbon-coated layer located on the surface of the current collector substrate, a rod-like structure is in-situ grown on the carbon-coated layer, and the rod-like structure includes a rod-like body and carbon particles embedded in the rod-like body.
[0124] The current collector substrate is aluminum foil, and the material of the rod-shaped body is NiMoO4.
[0125] The rod-like structures appear as straws on the carbon coating layer, wherein the straws are: a plurality of the rod-like structures are clustered and divergent, and an angle θ between the rod-like structures and the plane of the carbon coating layer is mainly in the range of 30°-90°.
[0126] The rod-like structure is a prismatic microrod with a rectangular cross section. The length of the rectangle is in the range of 0.03 μm-0.07 μm, the width of the rectangle is in the range of 0.02 μm-0.06 μm, and the rod length of the rod-like structure is in the range of 0.5 μm-1.2 μm.
[0127] This embodiment also provides a method for preparing the above-mentioned composite current collector, comprising the following steps:
[0128] (1) Preparation of carbon-coated current collector:
[0129] S1: Mix the modified polyacrylic acid glue with water, and slowly stir at a speed of 600 rpm for 30 minutes to obtain a diluted polyacrylic acid glue (viscosity of 800 mPa·s).
[0130] S2: First dispersion: using carbon powder as a conductive agent, 50% of the conductive agent is added to the glue obtained in step S1, and the mixture is dispersed at a high speed of 2300 rpm for 60 minutes.
[0131] S3 Second dispersion: Continue to add 50% of the conductive agent and disperse at a high speed of 2250 rpm for 70 minutes.
[0132] S4 third dispersion: add water to reduce the viscosity of the slurry to prevent the slurry from being too viscous to be dispersed evenly, and disperse at a high speed of 2600rpm for 30min.
[0133] S5 tests the slurry pH and adjusts the slurry pH to 7 with water and sodium bicarbonate. This is because a slurry pH > 7 will cause a sharp increase in viscosity.
[0134] S6 was fully stirred and dispersed, and the slurry was dispersed at a high speed of 2250 rpm for 60 min.
[0135] S7: Add a wetting agent (modified polyether siloxane) in an amount of 10% of the total mass of the reaction system. After adding, slowly stir at 15 rpm for 40 minutes. Vacuum to remove bubbles, and homogenize at a pressure of 450 bar to obtain a carbon-coated slurry.
[0136] S8: coating the carbon-coated slurry obtained in step S7 on the surface of the aluminum foil, and forming a carbon-coated layer on the surface of the aluminum foil after drying to obtain a carbon-coated current collector.
[0137] (2) NiSO4·6H2O, Na2MoO4·2H2O and NMP are mixed to obtain a mixed salt solution, wherein the molar ratio of nickel element to molybdenum element is 3.5:1.
[0138] (3) The mixed salt solution obtained in step (2) and the carbon-coated current collector obtained in step (1) are placed in a Teflon high-pressure reactor, and the carbon-coated current collector is gently opened from the bottom of the reactor to suspend it in the solution. The reactor is sealed and reacted at 160°C for 15 hours. The pressure in the reactor is 2 atmospheres. After cooling to room temperature, the sample is taken out, placed in an oven, and dried at 60°C for 12 hours to obtain a composite current collector.
[0139] Example 4
[0140] This embodiment provides a composite current collector and a preparation method thereof, wherein the molar ratio of NiSO4·6H2O:Na2MoO4·2H2O is 1:1, and the rest is the same as in Embodiment 1.
[0141] Example 5
[0142] This embodiment provides a composite current collector and a preparation method thereof, wherein the molar ratio of NiSO4·6H2O:Na2MoO4·2H2O is 1.5:1, and the rest is the same as in Embodiment 1.
[0143] Example 6
[0144] This embodiment provides a composite current collector and a preparation method thereof, wherein the molar ratio of NiSO4·6H2O:Na2MoO4·2H2O is 2:1, and the rest is the same as in Embodiment 1.
[0145] Example 7
[0146] This embodiment provides a composite current collector and a preparation method thereof, wherein the molar ratio of NiSO4·6H2O:Na2MoO4·2H2O is 3:1, and the rest is the same as in Embodiment 1.
[0147] Example 8
[0148] This embodiment provides a composite current collector and a preparation method thereof, wherein the molar ratio of NiSO4·6H2O:Na2MoO4·2H2O is 5:1, and the rest is the same as in Embodiment 1.
[0149] Example 9
[0150] This embodiment provides a composite current collector and a preparation method thereof, wherein the molar ratio of NiSO4·6H2O:Na2MoO4·2H2O is 7:1, and the rest is the same as in Embodiment 1.
[0151] Example 10
[0152] This embodiment provides a composite current collector and a preparation method thereof. The preparation method is different from that of Embodiment 1 in that the water in step S1 is replaced by NMP, and the NMP in step (2) is replaced by water.
[0153] Embodiment 11
[0154] This embodiment provides a composite current collector and a preparation method thereof. The preparation method is different from that of Embodiment 1 in that the Na2MoO4·2H2O in step (2) is replaced by ammonium molybdate, resulting in a pH value of 6 for the prepared mixed salt solution.
[0155] Comparative Example 1
[0156] This embodiment provides a composite current collector and a preparation method thereof. The preparation method is different from that of Embodiment 1 in that in step (3), 180° C. is replaced by 100° C.
[0157] In this comparative example, the reaction temperature was too low, so the straw-like structure could not be grown.
[0158] Comparative Example 2
[0159] This embodiment provides a composite current collector and a preparation method thereof, wherein the molar ratio of NiSO4·6H2O:Na2MoO4·2H2O is 1:0, and the rest is the same as in Embodiment 1.
[0160] test:
[0161] (1) Preparation of positive electrode sheet:
[0162] 1. According to the mass ratio of PVDF: lithium iron phosphate: carbon black = 2:97:1, PVDF, lithium iron phosphate and carbon black are dispersed in the solvent NMP to prepare a positive electrode slurry with a solid content of 50%;
[0163] 2. Apply the positive electrode slurry on the carbon-coated aluminum foil and bake at 120°C for 20 minutes;
[0164] 3. The electrode is 2.35g / cm 2 The positive electrode active material and the carbon-coated aluminum foil are pressed together by roller pressing to obtain a positive electrode sheet;
[0165] 4. Cut the positive electrode sheet into 12cm×2cm and place it in a vacuum drying oven for later use.
[0166] (2) Positive electrode peeling force test:
[0167] The prepared positive electrode sheet was attached to the test board with 2 cm 3M double-sided tape, the active material on the positive electrode sheet was separated from the carbon-coated layer, and the tape was attached to the carbon-coated aluminum foil, and the 180° positive electrode peeling force was tested on a tensile test machine.
[0168] (3) Carbon coating peeling force test method:
[0169] Cut the carbon-coated aluminum foil into 12cm×5cm size, stick the sample on the test board with 3M double-sided tape, and then stick the tape on the surface of the carbon-coated sample. Squeeze out the bubbles in the tape and perform the peeling force test of the carbon-coated layer on a tensile testing machine.
[0170] The test results are shown in Table 1.
[0171] Table 1
[0172]
[0173]
[0174] As shown in Table 1, the present invention increases the complexity and roughness of the surface by in-situ growing a rod-like structure of a specific composition on the carbon-coated layer of the carbon-coated current collector, increases the contact area and embedding degree with the positive electrode active material during rolling, and the positive electrode active material and the carbon-coated layer can be better combined, effectively improving the adhesion and peeling strength between the current collector and the positive electrode active material. At the same time, since carbon particles are embedded in the rod-like body, the composite current collector is guaranteed to have good conductivity, which is conducive to improving the electrochemical performance of the electrode prepared using it.
[0175] At the same time, by comparing Example 1 with Examples 4-9, it can be seen that the molar ratio of nickel and molybdenum will affect the micromorphology of the carbon coating layer on the surface of the current collector, the peeling force between the carbon coating layer and the positive electrode and the battery impedance, and thus affect the performance of the battery. If the nickel content is too low, the number and density of the rod-like structure will be reduced; if the nickel content is too high, the number of microrods will be too large, the toughness of the current collector will be reduced, and the peeling force between the carbon coating layer and the positive electrode will be reduced.
[0176] By comparing Examples 1 and 11, it can be seen that if sodium molybdate is replaced with ammonium molybdate, since the pH of the solution obtained by dissolving ammonium molybdate in the solvent is 6, the acidity is too strong, which is not conducive to the regulation of the morphology, thereby resulting in a decrease in the peeling force of the carbon coating layer and the positive electrode.
[0177] By comparing Example 1 with Comparative Example 1, it can be seen that if the reaction temperature is too low, the straw-like structure cannot be grown, thereby affecting the peeling force of the carbon coating layer and the positive electrode and the battery impedance.
[0178] By comparing Example 1 with Comparative Example 2, it can be seen that if molybdenum salt is not used in the preparation process, the peeling force of the carbon coating layer and the positive electrode will be greatly reduced.
[0179] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite current collector, characterized in that: The composite current collector includes a carbon-coated current collector, which includes a current collector substrate and a carbon-coated layer located on the surface of the current collector substrate, a rod-like structure is in situ grown on the carbon-coated layer, and the rod-like structure includes a rod-like body and carbon particles embedded in the rod-like body, and the material of the rod-like body includes Ni and Mo.
2. The composite current collector according to claim 1, characterized in that: The material of the rod-shaped body is doped or undoped NiMoO4, wherein the doping element is at least one of P, S, C or Se; Preferably, the rod-like structure appears as a straw on the carbon coating layer, and the straw-like shape means that a plurality of the rod-like structures are clustered and divergent, and an angle θ between the rod-like structure and the plane of the carbon coating layer is mainly in the range of 30°-90°; Preferably, the rod-like structure is a prismatic microrod with a rectangular cross section, the length of the rectangle is in the range of 0.03 μm-0.07 μm, the width of the rectangle is in the range of 0.02 μm-0.06 μm, and the rod length of the rod-like structure is in the range of 0.5 μm-1.2 μm; Preferably, the angle θ is in the range of 45°-90°, more preferably in the range of 60°-90°.
3. A method for preparing a composite current collector as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) preparing a mixed salt solution using nickel salt, molybdenum salt and solvent; (2) placing the mixed salt solution and the carbon-coated current collector in a reaction container, sealing the reaction container and heating it, and reacting them at a certain temperature and pressure to obtain the composite current collector.
4. The preparation method according to claim 3, characterized in that: The nickel salt in step (1) includes NiSO4·6H2O; Preferably, the molybdenum salt in step (1) includes Na2MoO4·2H2O and / or ammonium molybdate; Preferably, in step (1), the molar ratio of the nickel element in the nickel salt to the molybdenum element in the molybdenum salt is greater than or equal to 1.5:1, preferably (1.5-6):1; Preferably, the pH of the mixed salt solution in step (1) is 6.5-7.5; Preferably, when the solvent used in the preparation process of the carbon-coated current collector is water, the solvent in step (1) includes at least one of dimethylformamide, N-methylpyrrolidone and methyl ethyl ketone; Preferably, when the solvent used in the preparation process of the carbon-coated current collector is an oil-based solvent, the solvent in step (1) is water; Preferably, the oil-based solvent includes N-methylpyrrolidone; Preferably, when the carbon-coated current collector is a sodium electro-coating current collector, and the carbon-coated slurry used in the preparation process of the sodium electro-coating current collector contains a cross-linking agent, the solvent in step (1) is water; Preferably, the cross-linking agent includes at least one of methacrylic acid, methvinyl acid and isopropyl acrylic acid.
5. The preparation method according to claim 3 or 4, characterized in that: In step (2), heating to 120°C-240°C; Preferably, during the reaction in step (2), the pressure in the reaction container is 2-3 atmospheres; Preferably, the reaction time in step (2) is 8h-18h; Preferably, after the reaction in step (2), sampling and drying steps are also performed.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The method for preparing the carbon-coated current collector in step (2) comprises the following steps: (A) dispersing the raw materials of the carbon coating layer in a solvent to obtain a carbon coating slurry; (B) coating the carbon-coated slurry on the surface of a current collector substrate, and forming a carbon-coated layer on the surface of the current collector substrate after drying to obtain the carbon-coated current collector.
7. The preparation method according to claim 6, characterized in that: The raw materials of the carbon coating layer in step (A) include a conductive agent and a binder; Preferably, the conductive agent includes carbon powder, and preferably also includes graphite powder; Preferably, the mass proportions of the carbon powder and the graphite powder in the conductive agent are 70%-100% and 0%-30% respectively; Preferably, the binder comprises at least one of acrylate, polyacrylic acid, modified polyacrylic acid or waterborne polyurethane, preferably modified polyacrylic acid; Preferably, the binder is a modified polyacrylic acid glue having a solid content of 15%-30%, and a viscosity of the modified polyacrylic acid glue of 200mPa.s-1500mPa.s; Preferably, the raw material of the carbon coating layer in step (A) further includes a wetting agent; Preferably, the wetting agent comprises at least one of polyether siloxane, modified polyether siloxane and alcohols, preferably modified polyether siloxane; Preferably, the amount of the wetting agent is 3%-20% of the total mass of the reaction system.
8. The preparation method according to claim 6 or 7, characterized in that: Step (A) comprises: S1 adds a conductive agent to the adhesive solution and disperses the conductive agent to obtain a first material; S2. adding a wetting agent to the first material, stirring and homogenizing the material to obtain a carbon-coated slurry; Preferably, step S1 comprises: firstly adding a part of the conductive agent to the adhesive glue, performing a first high-speed stirring, then adding the remaining conductive agent to the obtained material, and performing a second high-speed stirring; Preferably, the portion of the conductive agent accounts for 40%-60% of the total amount of the conductive agent; Preferably, the rotation speed of the first high-speed stirring is 2000rpm-2600rpm; Preferably, the first high-speed stirring time is 30min-60min; Preferably, the rotation speed of the second high-speed stirring is 2000rpm-2600rpm; Preferably, the second high-speed stirring time is 60min-90min; Preferably, the stirring speed in step S2 is 10rpm-15rpm; Preferably, the stirring time in step S2 is 30 min-45 min; Preferably, the pressure of the homogenization treatment in step S2 is 300 bar-600 bar; Preferably, the preparation method further comprises: After step S1 and before step S2, perform the following steps: (a) adding a solvent to the first material to reduce the concentration of the slurry, and dispersing at a high speed of 2000 rpm to 2600 rpm for 30 min to 45 min; (b) adjusting the pH of the slurry obtained in step (a) to 5-7 using a pH adjuster; Preferably, the added amount of the pH adjuster is 5wt%-10wt% of the adhesive glue.
9. A pole piece, characterized in that: The pole piece includes a current collector and an active layer arranged on the surface of the current collector, and the current collector is the composite current collector according to claim 1 or 2 or a composite current collector prepared by the method according to any one of claims 3-8.
10. A battery comprising a positive electrode sheet, a negative electrode sheet and a separator, characterized in that: The positive electrode sheet and / or the negative electrode sheet are selected from the electrode sheet described in claim 9.
Citation Information
Patent Citations
Preparation method for nano-rod iron molybdate electrode material of lithium ion battery
CN105261755A
Shape-controlled cobalt-molybdenum sulfide / graphene composite material used for supercapacitor as well as preparation method thereof
CN109637834A
High-roughness copper foil for negative electrode current collector of lithium ion battery, and preparation method of high-roughness copper foil
CN112421050A
Ni-Co-S / CoMoO4 nano composite material and electrochemical preparation method thereof
CN113436903A
Preparation method of negative carbon-coated current collector, negative pole piece containing negative carbon-coated current collector and application of negative pole piece
CN114843447A